2005
DOI: 10.1111/j.1365-2869.2004.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea‐related cognitive deficits and intelligence: an implication of cognitive reserve theory

Abstract: Cognitive deficits in patients with obstructive sleep apnea syndrome (OSAS) are well demonstrated, but the pathophysiology of these deficits is still controversial, as the relationship between OSA severity and cognitive deficits is usually weak. Our study considers the possible relationship between OSA-related cognitive deficits and the overall intellectual function of OSA patients. Forty-seven OSA patients and 36 normal individuals underwent a neuropsychological battery test assessing attention and alertness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 30 publications
4
94
0
3
Order By: Relevance
“…Untreated sleep disorders, therefore, may hamper a student's ability to learn new material well. Obstructive sleep apnea has been associated with cognitive deficits, 21 and treatment of OSA may 21 or may not 22 improve cognition. Less directly, poor sleep might impact learning by means of reduced motivation, compromised health, or depressed mood.…”
Section: Resultsmentioning
confidence: 99%
“…Untreated sleep disorders, therefore, may hamper a student's ability to learn new material well. Obstructive sleep apnea has been associated with cognitive deficits, 21 and treatment of OSA may 21 or may not 22 improve cognition. Less directly, poor sleep might impact learning by means of reduced motivation, compromised health, or depressed mood.…”
Section: Resultsmentioning
confidence: 99%
“…Memory, executive function, and psychomotor performance are also significantly impacted by SDB 16,18 ; however, the associations may be modified by premorbid intelligence. 47,48 Depression and, less consistently, anxiety may also be related to SDB, although the relationships are complex and likely bidirectional. 49,50 The current study findings showed that some people with higher premorbid intelligence displayed good cognitive functioning, despite their severe sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestively, while attentional and cognitive measures are impaired in both, a correlation between OSA and general intelligence has been observed only in children (O'Brien et al 2004;Alchanatis et al 2005;Gozal 2008). Thus, sleep fragmentation during a heightened period of brain maturation might cause more profound and long-lasting impairments.…”
Section: Negative Impacts Of Disrupted Sleep During Mammalian Developmentioning
confidence: 99%